2009
DOI: 10.1007/s11199-009-9586-8
|View full text |Cite
|
Sign up to set email alerts
|

Risky Situation or Harmless Fun? A Qualitative Examination of College Women’s Bad Hook-up and Rape Scripts

Abstract: College students appear to be increasingly engaging in casual, non-committed sexual relationships, which may represent potential situations in which sexual assaults occur. The current study sought to assess if college students regard rape as a potential outcome of hooking up through examination of students' rape and hook-up scripts. A multi-ethnic sample of 109 US college women (54% European American, 19% Latina, 21% African American) described a typical rape and bad hook-up. Hook-up scripts generally did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
127
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(131 citation statements)
references
References 44 publications
4
127
0
Order By: Relevance
“…Furthermore, men who watched an R-rated video clip showing women as sexual objects (rather than a cartoon video clip) before reading about a date-rape scenario were more likely to agree that the woman derived pleasure from the rape and "got what she wanted" (Milburn et al 2000). Stereotypic views of date rape were also held by college women and low-income European-American and Latina women, who rated violent assaults by strangers as being more commonplace than assaults in a dating context or within an established relationship (Littleton et al 2007(Littleton et al , 2009.…”
Section: Cultural Scriptsmentioning
confidence: 99%
“…Furthermore, men who watched an R-rated video clip showing women as sexual objects (rather than a cartoon video clip) before reading about a date-rape scenario were more likely to agree that the woman derived pleasure from the rape and "got what she wanted" (Milburn et al 2000). Stereotypic views of date rape were also held by college women and low-income European-American and Latina women, who rated violent assaults by strangers as being more commonplace than assaults in a dating context or within an established relationship (Littleton et al 2007(Littleton et al , 2009.…”
Section: Cultural Scriptsmentioning
confidence: 99%
“…Indeed, despite the supposed greater freedom women have in Western society in expressing their sexuality and engaging in casual sex, there still appears to be a sexual double standard where the social implications for engaging in sexual behaviors (e.g., having sex with multiple or casual partners, engaging in particular sexual acts) differ for men and women (Smith et al 2008). For example, in a recent qualitative study conducted by myself and my colleagues (Littleton et al 2009c), we asked U.S. college women to describe a typical bad "hook-up" (generally regarded as a one-time sexual encounter with someone with whom you have no prior romantic relationship; Paul and Hayes 2002). While the majority of women reported that they had engaged in hooking-up (68%), they also believed that hooking-up could result in a number of negative consequences for women.…”
Section: Sexuality and Gendermentioning
confidence: 99%
“…Indeed, over half of the participants stated that a typical bad hook-up resulted in the woman experiencing feelings of shame, embarrassment or regret, as well as damage to her reputation. In contrast, men were often described as bragging to friends about the hookup and experiencing an enhanced sexual reputation as a result (Littleton et al 2009c). Paul and Hayes (2002) similarly found in a qualitative study of U.S. men's and women's worst hook-up experiences that women reported feelings of shame, self-blame, and regret that their partner never contacted them again, while men felt regret for choosing an unattractive partner or one with a negative sexual reputation.…”
Section: Sexuality and Gendermentioning
confidence: 99%
“…An article by Littleton et al (2009) provides an example of such an approach, which by asking subjects for two separate narrative accounts, may have encouraged this very discrepancy. 19 Having been asked to produce a script imagining a ''bad hook-up'' scenario and a separate script 19.…”
Section: A Criticisms Of Rape Scripts Researchmentioning
confidence: 99%
“…However, since the real rape myth anticipates a rapist to be the opposite of a committed sexual partner (i.e., a stranger), does crediting such beliefs and practises with legitimacy and lawfulness amount to endorsing the myth? Certainly it is because mock jurors look to signs of a pre-existing sexual relationship in discrediting a complainant's account that they are criticized for indulging in rape myth acceptance (Ellison & Munro, 2009Littleton et al, 2009;Littleton, 2011). And in cases in which consent is in doubt and in which the accused tries to use the prior existence of a sexual relationship to bolster his defense, 22 appeal judges and (for example) media commentators have been criticized as endorsing the myth that heterosexual relationships are a context in which safety may be anticipated (Busby, 2012;Gotell, 2012;Craig, 2014).…”
Section: B Criticisms Of Mock-jury Researchmentioning
confidence: 99%